Direct Isolation of Seamless Mutant Bacterial Artificial Chromosomes. Issue 1 (3rd April 2017) - Lyozin, George T.; Kosaka, Yasuhiro; Bhattacharje, Gourab; Yost, H. Joseph; Brunelli, Luca
Abstract: Seamless (i.e., without unwanted DNA sequences) mutant bacterial artificial chromosomes (BACs) generated via recombination‐mediated genetic engineering (recombineering) are better suited to study gene function compared to complementary DNA (cDNA) because they contain only the specific mutation and provide all the regulatory sequences required for in vivo gene expression. However, precisely mutated BACs are typically rare (∼1:1, 000 to 1:100, 000), making their isolation quite challenging. Although these BACs have been classically isolated by linking the mutation to additional genes, i.e., selectable markers, this approach is prone to false positives and is labor‐intensive because it requires the subsequent removal of the selectable marker. We created Founder Principle–driven Enrichment (FPE), a method based on the population genetics "founder principle, " to directly isolate rare mutant BACs, without any selectable marker, from liquid cultures via the polymerase chain reaction (PCR). Here, we provide a detailed description of FPE, including protocols for BAC recombineering and PCR screening. © 2017 by John Wiley & Sons, Inc.